The fall of Berlin - Mann, Mendel 1916-1975 (Open Book Publishers, 2020)
"Mendl Mann's autobiographical novel The Fall of Berlin tells the painful yet compelling story of life as a Jewish soldier in the Red Army. Menakhem Isaacovich is a Polish Jew who, after fleeing the Nazis, finds refuge in the USSR. The novel follows Menakhem as he fights on the front line in Stalin's Red Army against Hitler and the Nazis who are destroying his homeland of Poland and exterminating the Jews. Menakhem encounters anti-Semitism on various occasions throughout the narrative, and struggles to comprehend how seemingly normal people could hold such appalling views. As Mann writes, it is odd that "vicious, insidious anti-Semitism could reside in a person with elevated feelings, an average person, a decent person". The Fall of Berlin is both a striking and timely look at the struggle that many Jewish soldiers faced. Skillfully translated from Yiddish and introduced by Maurice Wolfthal, this is an affecting and unique book which eloquently explores a variety of themes - anti-Semitism, patriotism, Stalinism and life as a Jewish soldier in the Second World War. The Fall of Berlin is essential reading for anyone interested in the Yiddish language, Jewish history, and the history of World War II."--Provided by publisher
Translated from the Yiddish
Includes mainly a translation of Dos faln un Berlin published by Bikher Farlag, 1960
Keywords: Sowjetunion -- Raboče-Krestʹjanskaja Krasnaja Armija; Geschichte 1945; Juden; Russlandfeldzug -- 1941-1945; Soldat; Berlin, Battle of, Berlin, Germany, 1945 / Fiction; Germany / Berlin; Mann, Mendel / 1916-1975 / Fiction; Soviet Union / Raboche-Krestʹi͡anskai͡a Krasnai͡a Armii͡a / Fiction; Yiddish fiction / Translations into English; Jewish soldiers / Soviet Union / Fiction; Antisemitism / Soviet Union / Fiction; Holocaust, Jewish (1939-1945) / Poland / Fiction; 1945; 1939-1945; Fiction; Personal narratives / Jewish; Yiddish fiction; Autobiographical fiction; Autobiografie; Fiktionale Darstellung